EXTENSIVE LISTENING AND VIEWING IN ELT - Francisca M. Ivone; Willy A. Renandya (TEFLIN Journal, 2019)
Inspired by the success and informed by the principles of the Extensive Reading (ER) approach, Extensive Listening (EL) and Viewing have started to gain the attention of both L2 researchers and practitioners. The purpose of this paper is to examine the theoretical and research base of EL and the extent to which it is similar to or different from ER, discuss its language learning benefits for L2 students in different learning contexts, and explore different ways EL can be productively implemented in the classroom. Practical suggestions on how to source for freely available EL materials on the Internet and how these can be pedagogically used to enhance language proficiency are also offered. We believe that EL, when systematically implemented, can not only enhance students' listening skills but also have a positive influence on the students' overall language development.